Differences in certain typical performance indicators at five consecutive men's European Handball Championships held in 2002, 2004, 2006, 2008 and 2010 - Sibila, M.; Bon, M.; Mohoric, U.; Pori, P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Most interesting playing performance indicators were selected from five consecutive Men`s European Championships held in the period from y. 2002 to 2010. We calculated descriptive statistics and differences among ECh. From obtained results we may conclude that there are many statistically significant differences in the performance indicators among the present ECh. That reveal some developing trends in contemporary Handball.